Observation of two N2‐isobutyrylguanine tautomers by NMR spectroscopy. (20th November 2012) - Yang, Lijing; Li, Jia; Simionescu, Razvan; Yan, Hongbin
<x xml:space="preserve">Abstract</x> N 2‐Isobutyrylguanine was prepared by treatment of guanine with isobutyryl chloride. Two tautomers, 1, 7‐dihydro‐2‐(isobutyroyl)amino‐6H‐purin‐6‐one and 1, 9‐dihydro‐2‐(isobutyroyl)amino‐6H‐purin‐6‐one, were identified in almost 1 : 1 ratio in dichloromethane–dimethyl sulfoxide (1 : 1 v/v) by NMR spectroscopy. By using the selective‐inversion experiments, enthalpy, entropy, and free energy for activation were determined. This work represents the first report of guanine tautomers observed directly by NMR spectroscopy. Copyright © 2012 John Wiley & Sons, Ltd.